Improving community knowledge and motivation to vaccinate COVID-19 - Etha Rambung; Mellyanawati Mellyanawati; Glory Ta’bi Palloan; Angelarita Djami Raga (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Vaccination against COVID-19 is the best option to prevent COVID-19. Therefore, the government continues to strive so that the entire community gets the COVID-19 vaccination to break the chain of transmission and at the same time form herd immunity. The coordinator of the congregation of the Oikos Prosevchomai church, Prambon Subdistrict, Sidoarjo Regency hopes that all congregations get vaccinated. However, there are still some members who are still hesitant to vaccinate because they do not understand the COVID-19 vaccine, the importance of following the COVID-19 vaccination, and implementing health protocols. Because accurate information about vaccination is inadequate, hoax news is circulating more. The purpose of this activity is to improve the knowledge and motivation of participants in preventing transmission and vaccination of COVID-19. The method of activity is education on the COVID-19 vaccine, training on how to carry out the correct health protocol, and consulting assistance on vaccinations. The results of the activity showed that education, training, and assistance for COVID-19 prevention and vaccination improved participants' knowledge and motivation toward vaccination and implementation of COVID-19 health protocols.